ROLE OF INTERLEUKIN-1 IN OSTEOARTHROSIS AND POSSIBILITIES OF ITS ARREST - Rimma Mikhaylovna Balabanova; Rimma Mikhailovna Balabanova (Современная ревматология, 2011)
Research Institute of Rheumatology, Russian Academy of Medical Sciences, Moscow The study of the pathogenesis of primary osteoarthrosis (OA) allows it to be considered as a chronic inflammatory disease in which proinflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor-α(TNF-α), the expression of which is observed in the subchondral bone, cartilage, and synovium even in the absence of clinical signs of inflammation, are of great importance. The severity of OA and its site depend on IL-1 gene polymorphism. The mechanism of action of IL-1 in OA is to activate osteoclasts, to enhance the expression of calcium, and to modulate pain mediators, resulting in cartilaginous plate and subchondral bone destructions. The inhibition of IL-1 generation and activity requires the use of diacerein, the mechanism of whose action is to suppress the synthesis of cytokines and to reduce the number of their receptors onto the surface of chondrocytes, which lowers their sensitivity to IL-1. The drug intracellularly blocks nuclear factor NFκB activation, by diminishing the expression of the genes responsible for the production of other proinflammatory cytokines. Clinical trials have provided evidence for the symptomatic and structure-modifying activities of diacerein that has, in addition, an aftereffect, i. e. the effect is retained even after the drug is discontinued.